PENGGUNAAN METODE IMPROVE UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MEMECAHKAN MASALAH PADA MATERI LARUTAN PENYANGGA, KELARUTAN DAN HASILKALI KELARUTAN DI KELAS XI IPA 4 SMA NEGERI 1 BANJARMASIN - Rahmat Eko Sanjaya; Syahmani Syahmani; Bambang Suharto (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2014)
Abstract: Use of IMPROVE method to increase student’s ability in problem solving of the buffer, solubility and solubility product at class XI IPA 4 SMAN 1 Banjarmasin School Year 2012/2013. A study concerning the use of the IMPROVE in buffer, solubility and solubility product. This study aims to determine the increase in students' ability in problem solving, both cognitive achievement and metacognitive development. Study using action research design with 2 cycles. Each cycle consists of planning, action, observation and reflection. The subjects were students of class XI IPA 4 SMA Negeri 1 Banjarmasin with the number 34. Data were collected using a test problem-solving ability and other non-test instruments to determine the implementation of the action. Data were analyzed by quantitative descriptive analysis and qualitative analysis. The results showed that the application of IMPROVE method can improve students' ability to solve the problems of the average 37.96 to 61.83 in the first cycle to the second cycle. Cognitive learning outcomes of students on average 54.74 to 93.79 in the first cycle to the second cycle. Metacognitive development of students hasincreased from category Still Very Risky (SVR) in the first cycle to Start Growing (SG) in the second cycle. An increase in activity of teachers in the implementation of the action category quite well in the first cycle to be good in the second cycle. Student activity increased in the first cycle of category good enough to be good on the second cycle. Student responses on the first and second cycle showed excellent criterion.Keywords: IMPROVE method, metacognitive, problem-solving ability